Synthesis and Characterization of Non-Lead based Multiferroic Composites - Amritpal (My University, 2015)
Multiferroic materials are of particular interest due to their long range of applications in sensors, phase shifters, transducers, and memory devices. Non-Lead based ME composites have recently drawn increasing interest because they are non-toxic in nature and environmental friendly. Pure BNT-BKT-BMgT and CZFMO and composite BNT-BKT-BMgT-CZFMO have been prepared by using sol-gel technique. The structural, magnetic, ferroelectric and morphological properties have been investigated and discussed. The study of ferroelectric behavior of pure BNT-BKT-BMgT and composites show the decrease value of saturation polarization for composite are observed due to low resistivity of ferrite phase. The magnetic study of pure CZFMO and composites 72.5BNT-22.5BKT-5BMgT show the well saturated M-H loop indicates the ferromagnetic nature of samples. The corecivity of the sample increased from ~ 260 Oe for pure CZFMO to ~ 48 Oe for composite (x=0.2). The corecivity of the samples confirmed the soft magnetic nature of the sample.
M.Sc. (Physics)
Keywords: Multiferroics; Composite multiferroices; Non-lead based composite ME materials; SPMS